GPla Polymorphisms Are Associated with Outcomes in Patients at High Cardiovascular Risk - Rath, Dominik; Schaeffeler, Elke; Winter, Stefan; Levertov, Semjon; Müller, Karin; Droppa, Michal; Stimpfle, Fabian; Langer, Harald F.; Gawaz, Meinrad; Schwab, Matthias; Geisler, Tobias (Frontiers in Cardiovascular Medicine, 2017)
Background: Platelet membrane glycoprotein receptors mediate thrombus formation. GP Ia/IIa is an essential platelet integrin receptor. Single nucleotide polymorphisms (SNPs) of the GP Ia/IIa gene alter GP Ia/IIa expression, however their influence on cardiovascular disease remains unclear. This study aimed to investigate the effect of the GP Ia/IIa SNPs rs1126643 and rs1062535 on clinical outcomes in a large collective including high risk patients with cardiovascular disease. Methods and results: GP Ia SNP analysis was performed in 943 patients with symptomatic coronary artery disease. All patients were tracked for all cause death, myocardial infarction and ischemic stroke for 360 days. Homozygous carriers of the minor allele showed significantly worse event-free survival when compared with major allele carriers in the complete collective as well as in the subset of high risk patients (carrying all of the following three risk factors: diabetes type II, hypertension and hyperlipidaemia). There was no significant difference in the subset of low risk patients (carrying none of the three risk factors). CONCLUSIONS: GPla SNPs are associated with cardiovascular prognosis especially in high risk patients. Identification of GPIa SNPs are of importance to tailor therapies in patients at already high cardiovascular risk.